Determinants of clove exports in Zanzibar: Implications for policy - Samwel J. Kabote; Jires Tunguhole (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper analyses factors for the declining trend in clove exports in Zanzibar using time series data that were collected between 1980 and 2020 and analysed using the vector error correction model, complemented with qualitative analysis. Clove production, producer price, world price, gross domestic product, and the exchange rate showed positive statistically significant impacts in the long run at the one per cent level, while foreign direct investment, population growth rate, rainfall, and gross capital formation showed significant negative association. Inflation had no impact. Some factors affected clove exports indirectly through production. Extension services were poor while the local price of cloves was low and not stable. We can conclude that clove exports were determined by many interlinked factors. We recommend an integrated policy approach that takes on board, comprehensively, all determining factors to improve and sustain clove exports.
Keywords: C22; Q01; Q11; Q17; 330; cloves; exports; vector error correction model; Zanzibar